Drosophila Kruppel homolog 1 represses lipolysis through interaction with dFOXO. Issue 1 (December 2017) - Kang, Ping; Chang, Kai; Liu, Ying; Bouska, Mark; Birnbaum, Allison; Karashchuk, Galina; Thakore, Rachel; Zheng, Wenjing; Post, Stephanie; Brent, Colin; Li, Sheng; Tatar, Marc; et al.
Abstract Transcriptional coordination is a vital process contributing to metabolic homeostasis. As one of the key nodes in the metabolic network, the forkhead transcription factor FOXO has been shown to interact with diverse transcription co-factors and integrate signals from multiple pathways to control metabolism, oxidative stress response, and cell cycle. Recently, insulin/FOXO signaling has been implicated in the regulation of insect development via the interaction with insect hormones, such as ecdysone and juvenile hormone. In this study, we identified an interaction betweenDrosophila FOXO (dFOXO) and the zinc finger transcription factor Kruppel homolog 1 (Kr-h1), one of the key players in juvenile hormone signaling. We found thatKr-h1 mutants show delayed larval development and altered lipid metabolism, in particular induced lipolysis upon starvation. Notably, Kr-h1 physically and genetically interacts with dFOXOin vitro andin vivo to regulate the transcriptional activation of insulin receptor (InR ) and adipose lipasebrummer (bmm ). The transcriptional co-regulation by Kr-h1 and dFOXO may represent a broad mechanism by which Kruppel-like factors integrate with insulin signaling to maintain metabolic homeostasis and coordinate organism growth.